Citizenship Questions and Environmental Crisis in the Niger Delta: A Critical Reflection (Nordic Journal of African Studies, 2002)
On a global proportion, human activities are altering the composition, nature and texture of the environment. It is often argued that in the absence of man, these environmental changes would take place. However, what is of concern today is the pace of the change and the relationship between the presence of man and his deleterious impacts on the environment.One of the very important subject matter increasingly gaining attention on its own right as a result of the impact of globalization is the question of citizenship rights and privileges. In developing countries of Africa, like Nigeria, the impact of globalization on citizenship notions is threatening. The emergence of an ever-expanding global world order and its interest in environmental resources has created an alarming dichotomy in citizenship notions especially in the wake of the Ogoni crisis in November 1995.This paper attempts a critical interpretation of the crisis in the Niger Delta of Nigeria in the light of citizenship questions. It concludes that such an interpretation allows for the transcending of boundaries on citizenship claims and stakes. It also provides the bridgehead for proffering certain categorical imperatives that will ensure peace.